Ultrathroughput immunomagnetic cell sorting platform. Issue 24 (16th November 2022) - Philpott, David N.; Chen, Kangfu; Atwal, Randy S.; Li, Derek; Christie, Jessie; Sargent, Edward H.; Kelley, Shana O.
Abstract : High-throughput phenotypic cell sorting is critical to the development of cell-based therapies and cell screening discovery platforms. Abstract : High-throughput phenotypic cell sorting is critical to the development of cell-based therapies and cell screening discovery platforms. However, current cytometry platforms are limited by throughput, number of fractionated populations that can be isolated, cell viability, and cost. We present an ultrathroughput microfluidic cell sorter capable of processing hundreds of millions of live cells per hour per device based on protein expression. This device, a next-generation microfluidic cell sorter (NG-MICS), combines multiple technologies, including 3D printing, reversible clamp sealing, and superhydrophobic treatments to create a reusable and user-friendly platform ready for deployment. The utility of such a platform is demonstrated through the rapid isolation of mature natural killer cells from peripheral blood mononuclear cells, for use in CAR-NK therapies at clinically-relevant scale.